Hypoxic Stress-Induced Tumor and Immune Plasticity, Suppression, and Impact on Tumor Heterogeneity - Terry, Stéphane; Buart, Stéphanie; Chouaib, Salem (Frontiers in Immunology, 2017)
The microenvironment of a developing tumor is composed of proliferating cancer cells, blood vessels, stromal cells, infiltrating inflammatory cells and a variety of associated tissue cells. The crosstalk between stromal cells and malignant cells within this environment crucially determines the fate of tumor progression, its hostility and heterogeneity. It is widely accepted that hypoxic stress occur in most solid tumors. Moreover, cancer cells found within hypoxic regions are presumed to represent the most aggressive and therapy-resistant fractions of the tumor. Here, we review evidence that hypoxia regulates cell plasticity, resistance to cell-mediated cytotoxicity, and immune suppression. Exposure to hypoxia occurs as a consequence of insufficient blood supply. Hypoxic cells activate a number of adaptive responses coordinated by various cellular pathways. Accumulating data also suggest that hypoxic stress in the tumor microenvironment (TME) promotes tumor escape mechanisms through the emergence of immune resistant tumor variants and immune suppression. Thus, solid tumors seem to build up a hostile hypoxic microenvironment that hampers cell-mediated immunity and dampen the efficacy of the immune response.